2002
DOI: 10.1074/jbc.m207988200
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of MIN6 β Cells with TAT-Syntaxin SNARE Motif Inhibits Insulin Exocytosis in Biphasic Insulin Release in a Distinct Mechanism Analyzed by Evanescent Wave Microscopy

Abstract: To investigate the in vivo interaction of syntaxin-mediated soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptor (SNARE) assembly and insulin exocytosis in biphasic release, we examined the dynamics of insulin granule motion such as docking and fusion with the plasma membrane when the syntaxin SNARE motif (H3 domain) was transduced into living MIN6 ␤ cells. TAT-H3, produced by fusion of the protein transduction domain of human immunodeficiency virus-1 TAT to the syntaxin-H3 domain, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…The importance of syntaxin 1a in the tethering or docking process of insulin granules also is supported by recent findings from evanescent wave microscopy. Ohara-Imaizumi et al (14) have shown that introduction of the H3 domain of syntaxin 1a into MIN6 cells inhibits new docking events of insulin granules during the glucose stimulation. We have found that the H3 fragment of syntaxin 1a directly binds to granuphilin in vitro and that its introduction into MIN6 cells induces a concomitant decrease in newly docked granules and the amount of endogenous granuphilin-syntaxin 1a complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of syntaxin 1a in the tethering or docking process of insulin granules also is supported by recent findings from evanescent wave microscopy. Ohara-Imaizumi et al (14) have shown that introduction of the H3 domain of syntaxin 1a into MIN6 cells inhibits new docking events of insulin granules during the glucose stimulation. We have found that the H3 fragment of syntaxin 1a directly binds to granuphilin in vitro and that its introduction into MIN6 cells induces a concomitant decrease in newly docked granules and the amount of endogenous granuphilin-syntaxin 1a complex.…”
Section: Discussionmentioning
confidence: 99%
“…Transduction of MIN6 Cells with TAT Fusion Proteins-Isolation of TAT-GFP and TAT-H3 was performed as described previously (14). MIN6 cells were transduced for 50 min with 70 g/ml of TAT fusion proteins, and the cell extracts were prepared as described for the immunoprecipitation experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired, or even completely absent first-phase insulin secretion is an early feature of type 2 diabetes, whereas second-phase insulin secretion deteriorates with progression of the disease. Data from rodent models suggest that firstphase insulin secretion results from exocytosis of insulin granules already present at the plasma membrane, whereas second-phase secretion involves recruitment of insulin granules from the beta cell interior [12,13]. Triggering of biphasic insulin secretion requires generation of beta cell electrical activity, which results from a functional interplay between the beta cell ATP-sensitive K + channel (which, in part, is encoded by the KCNJ11 gene) and voltagedependent Ca 2+ channels (VDCC) [14].…”
Section: Introductionmentioning
confidence: 99%